2018
DOI: 10.1002/jcla.22599
|View full text |Cite
|
Sign up to set email alerts
|

Leucocyte telomere length and paroxysmal atrial fibrillation: A prospective cohort study and systematic review with meta‐analysis

Abstract: Our prospective data showed that leucocyte telomere length was similar between AF and non-AF patients but was significantly longer in male patients with PAF than those without AF in our subgroup analysis. Our meta-analysis found that t/s did not predict AF. These findings support the notion that chronological aging, but not markers of biological aging, predicts the risk of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
1
8
0
1
Order By: Relevance
“…One of the consequences is fibrosis, characterized by increased turnover of the extracellular matrix, producing conduction abnormalities that provide the necessary substrate for arrhythmogenesis . A number of blood biomarkers and electrocardiographic predictors have been found in association with AF onset, development, and recurrence. Of these, galectin‐3 plays a key role in acute and chronic pro‐inflammatory responses and mediates activation of quiescent fibroblasts and synthesis of collagen .…”
Section: Discussionmentioning
confidence: 99%
“…One of the consequences is fibrosis, characterized by increased turnover of the extracellular matrix, producing conduction abnormalities that provide the necessary substrate for arrhythmogenesis . A number of blood biomarkers and electrocardiographic predictors have been found in association with AF onset, development, and recurrence. Of these, galectin‐3 plays a key role in acute and chronic pro‐inflammatory responses and mediates activation of quiescent fibroblasts and synthesis of collagen .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although our MR study did not find evidence to support the associations between TL and heart failure or cardiac death, the ORs for these associations were both less than 1.0, suggesting that TL might be a potential risk factor for heart failure and cardiac death. Previous studies have shown inconsistent results in the associations of TL with heart failure, atrial fibrillation, and cardiac death (14,(51)(52)(53)(54)(55)(56)(57), indicating the need for further research.…”
Section: Discussionmentioning
confidence: 98%
“…Even though we did not find a relevant association between ECG measures and telomere length, it remains unresolved if telomere length is relevant for the pathophysiology of selected age-dependent conditions. At least for AF, a relation with telomere length has been suggested, but the results remain conflicting [33][34][35].…”
Section: Discussionmentioning
confidence: 99%